2015
DOI: 10.1007/s00405-015-3706-6
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for preventive treatments for early post-tympanostomy tube otorrhea in persistent otitis media with effusion

Abstract: Some studies have shown that post-tympanostomy tube otorrhea (PTTO) is a common complication after tympanostomy tube insertion. There are wide range of controversies about the incidence of PTTO and different methods of preventive treatment. The aim of this study was to determine the incidence of early PTTO in persistent otitis media with effusion in our centers. We also investigated the effect of preventive treatments on the incidence of early PTTO in children with persistent otitis media with effusion. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In a clinical trial 241 published after the Cochrane review, 291 children having tube insertion for chronic OME had their ears (N = 560) randomized into 4 groups for interventions to prevent postoperative otorrhea: (1) saline washout (irrigation) of the middle ear cavity, (2) oral amoxicillin for 7 days, (3) oral amoxicillin for 7 days plus ciprofloxacin ear drops for 3 days, or (4) observation (control). No significant differences were found among groups regarding postoperative otorrhea, which ranged from 1.1% to 2.3%.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…In a clinical trial 241 published after the Cochrane review, 291 children having tube insertion for chronic OME had their ears (N = 560) randomized into 4 groups for interventions to prevent postoperative otorrhea: (1) saline washout (irrigation) of the middle ear cavity, (2) oral amoxicillin for 7 days, (3) oral amoxicillin for 7 days plus ciprofloxacin ear drops for 3 days, or (4) observation (control). No significant differences were found among groups regarding postoperative otorrhea, which ranged from 1.1% to 2.3%.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…This suggests that irrigation and dilution may play an important role. Normal saline has been used intraoperatively as an irrigant, 2,6 but its use in the days after TTP as in our study has not been reported. We hypothesized that normal saline used during and after surgery would maintain tube patency and have similar ETTO rates to topical ciprofloxacin.…”
Section: Discussionmentioning
confidence: 87%
“…Prophylaxis against VTO is controversial, and there is little evidence available for prophylaxis against VTB 5 . Historic studies have investigated antiseptic preparation of the external ear canal prior to MEVT insertion, 10 insertion of antibiotic‐coated MEVTs, 11,12 postoperative oral antibiotic prophylaxis, 13 application of intraoperative and postoperative topical antibiotic or isotonic saline drops, 14 and intraoperative irrigation of the middle ear cleft 15 . Current best evidence supports the single application of intraoperative topical antibiotics and steroid, an extended application of topical antibiotic as well as saline irrigation of the middle ear for prophylaxis against otorrhoea 16,17 .…”
Section: Introductionmentioning
confidence: 99%